Microbiology of the Rapidly Changing Polar Environments - Eva Ortega-Retuerta (Frontiers Research Topics, 2018)
Marine and freshwater polar environments are characterized by intense physical forces and strong seasonal variations. The persistent cold and sometimes inhospitable conditions create unique ecosystems and habitats for microbial life. Polar microbial communities are diverse productive assemblages, which drive biogeochemical cycles and support higher food-webs across the Arctic and over much of the Antarctic. Recent studies on the biogeography of microbial species have revealed phylogenetically diverse polar ecotypes, suggesting adaptation to seasonal darkness, sea-ice coverage and high summer irradiance. Because of the diversity of habitats related to atmospheric and oceanic circulation, and the formation and melting of ice, high latitude oceans and lakes are ideal environments to investigate composition and functionality of microbial communities. In addition, polar regions are responding more dramatically to climate change compared to temperate environments and there is an urgent need to identify sensitive indicators of ecosystem history, that may be sentinels for change or adaptation. For instance, Antarctic lakes provide useful model systems to study microbial evolution and climate history. Hence, it becomes essential and timely to better understand factors controlling the microbes, and how, in turn, they may affect the functioning of these fragile ecosystems. Polar microbiology is an expanding field of research with exciting possibilities to provide new insights into microbial ecology and evolution. With this Research Topic we seek to bring together polar microbiologists studying different aquatic systems and components of the microbial food web, to stimulate discussion and reflect on these sensitive environments in a changing world perspective.